INVENTORY MANAGEMENT ANALYSIS USING THE MATERIAL REQUIREMENT PLANNING (MRP) METHOD IN THE OPTIMIZATION OF HANDICRAFT RAW MATERIALS - Suflani Suflani; Khaeruman Khaeruman; Masmanto Moh Jawahir (International Journal of Multidisciplinary Research and Literature, 2023)
Raw material inventory is a very important asset for a business. The inability to carry out effective planning of raw material inventory can have a negative impact on the production process. Research aimed at optimizing material inventory planning is a very important step to increase the efficiency of the production process. Qualitative analysis is indeed an important and relevant research method in optimizing material inventory planning. This method focuses on an in-depth understanding of the data collected, exploring the meaning of the information provided by informants through interviews, observation, or documentation. The MRP (Material Requirements Planning) method is an effective approach in optimizing material inventory planning. This method allows companies to place orders for raw materials precisely, determine the amount of goods to be purchased, and reduce the risk of delays in the supply of raw materials. The results of using the MRP method are: (1) being able to order raw materials precisely, because we already know what is needed, (2) can determine the amount of goods to be purchased, (3) reducing the risk of delays in the supply of raw materials